Pengaruh Penagihan Pajak dan Kepemilikan Nomor Pokok Wajib Pajak Terhadap Kesadaran Wajib Pajak dan Penerimaan Pajak di Kantor Pelayanan Pajak Pratama Gianyar - Tjokorda Gde Anggadhika Widya Pramana Putra (Public Inspiration : Jurnal Administrasi Publik, 2021)
From 2014 to 2018 the number of taxpayers registered at the Gianyar KPP Pratama continued to grow. The largest growth occurred in 2016, which was 9.26% and the smallest growth in 2018 was 7.59%. In terms of tax revenue, the highest increase in the realization of tax revenue growth at KPP Pratama Gianyar occurred in 2017, which was 39.06 %. In 2016, tax revenue growth decreased by 3.02 percent. This increase in revenue continued to occur in 2018, although the growth rate was not as high as 2017. This research motivation is to examine the role of mandatory ownership of NPWP, tax audit, collection of tax, and taxpayer awareness of tax revenue at KPP Pratama Gianyar. This is quantitative research, conducted by data analysis using SMART-PLS based on sample of taxpayers registered at KPP Pratama Gianyar. Results of the study at the KPP Pratama Giayar, concluded that direct tax collection actions have a positive and significant effect on increasing tax revenue. The obligation to have a NPWP directly has a positive and significant impact on the awareness of taxpayers. Direct tax revenues will be positively and significantly influenced by the awareness of taxpayers. With the mediated awareness of taxpayers, the effect of tax collection on tax revenues proved positive and significant, and obtain 1 (one) form of partial mediation. With the mediated awareness of taxpayers, the effect of NPWP ownership obligations on tax revenues is proven to be positive and significant, and obtain 1 (one) form of full mediation.